PSYCHOGRAPHIC AND BEHAVIOURAL SEGMENTATION OF WINE CONSUMERS - Krstić, Jelena; Radojičić, Milan; Veljović, Sonja (Economics of Agriculture, 2026)
The purpose of this article is to identify specific marketsegments of wine consumers based on their demographic,psychographic and behavioural characteristics. The data wascollected through an online survey of 269 wine consumersin Serbia. The data were analyzed by using multivariatestatistical methods (factor analysis and clustering) inconjunction with descriptive and inferential statistics (Chisquare test, one-way ANOVA, independent t-test). Threeconsumer segments were identified by applying a TwoStepcluster analysis: Casual consumers, Recommendationresponsive consumers and Wine enthusiasts. In terms ofdemographic characteristics, education, place of residenceand household type were found to be significantly differentamong consumer groups. Findings can be used as a basisfor the development of effective promotional campaignstargeted at specific consumer segments.